Pelaksanaan Proses Quality Control terhadap Kualitas dan Efisiensi Produksi di B21 Digital Printing - Lobie Habibie Aza Negara; Fani Khoirotunnisa (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The digital printing industry in Indonesia is growing rapidly along with technological advances. One The digital printing industry in Indonesia is growing rapidly along with technological advances. This study aims to determine the effect of Quality Control (QC) on production quality and efficiency at B21 Digital Printing. With a descriptive qualitative approach, data was collected through observation and interviews. The results show that the implementation of strict QC from raw material selection to final packing has a positive impact on product quality and operational efficiency. The existence of good Quality Control can minimize product defects, improve quality stability, and increase customer satisfaction. Operational efficiency is also affected by the reduction of time and resources wasted due to production errors. Thus, the implementation of QC at B21 Digital Printing is proven to be effective in improving production quality and efficiency.